GLYUTTONIYALÍQ DISKURSTÍŃ IZERTLENIWI - Nurlıbekova, G.M. (ILIM hám JÁMIYET, 2025)
This article discusses the concept of discourse in linguistics and the study of gluttonic discourse as one of its specific types. Numerous opinions and reflections of global linguists on discourse issues are analyzed. In particular, the necessity of studying discourse studies and gluttonic discourse in Karakalpak linguistics is substantiated.